Operations Strategy for Performance and Services Improvement of Maintenance Pumping Unit Team - HOOU PT. CPI - Wardhana, Satria Yoelis; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2015)
Abstract -PT. XYZ is expected by Government of Indonesia (GOI) to meet or exceed the oil production target. It’s required a strong maintenance program considering PT. XYZ is operating a brown field. There are lots of Pumping Units in X Field as very critical equipment to support production. The preventive/predictive maintenance (PM/PdM) program has been established and executed every 270 days/ Pumping Unit by 2 Business Partner. The main target from productions team is avoiding 7 Wells down every day and 170 Barrels Loss Production Opportunity (LPO). In monthly average those targets are achieved but sometimes the number of daily wells down is behind the target. There are also some gaps in executing maintenance activities such as no dedicated quality inspector, lack of supervision in the field, long duration to repair gearbox, unbalanced work load personnel, and no integrated contract execution and monitoring system.The new operations strategy is proposed to improve the performance and services of Maintenance Pumping Unit (MPU). The methodology used in this final project is study literature and team discussion. The existing resources and operations processes/capabilities are analyzed using Operations Strategy Framework Slack and Lewis (2008) to understand current conditions in MPU teams. The proposed improved operations strategy are implementation of Total Quality Management (TQM), improve work load distribution, finalize Roles & Responsibilites (R&R) within Project Business Support (PBS) and MPU Team, monitor phase control of LS Reduce PU Down Time due to Gear Box Failure, and development of Contract Cost Management System (CCMS). The benefit of implementing proposed operations strategy is potential cost saving 8,576 bbl oil or $428,800 using assumption oil price $50. The support from Wells and Facility Maintenance (WFM) leadership, capability and accountability from every PIC, monitoring process, and mitigation plan are some of the key success factors in the implementation stage to attain world class maintenance performance.Keywords: Operations strategy, maintenance pumping unit, PT. XYZ, wells down, loss production opportunity.